Method of Teaching Writing to the Seventh Grade Students of SMPM 25 Boarding School Pondok Modern Muhammadiyah Paciran Lamongan - Irmawati, Yuli, Aryati Prasetyarini, S.Pd, M.Pd, Dr. Dwi Haryanti, M.Hum (2015)
This research paper is conducted to describe the method of teaching writing to the seventh grade students in SMPM 25 Boarding School Pondok Modern Muhammadiyah Paciran Lamongan. In this research, the writer uses descriptive qualitative research. The data are taken from English learning process of writing skill. There are three methods of collecting data, are: observation, interview, and documentation. The techniques for analyzing data are: data reduction, data display and conclusion drawing/verification. In this research, there are some pints of the result, the first is based on observation, the method in teaching writing to the seventh grade is inquiry-based learning. The goal of teaching is to emphasize develop students' skills in using English as a communication tool. The material of teaching writing is descriptive text and taken from work sheet entitled Fokus "Bahasa Inggris" publisher by CV Sindunata, internet, and "English in Focus for Grade VII Junior High School (SMP/MTS)" publisher by Pusat Perbukuan Departemen Pendidikan Nasional. The procedures of teaching writing are: pre-teaching, while-teaching, and post-teaching. The writer found 2 techniques applied in teaching learning process, namely group writing and individual writing. Limited time and vocabulary, and boredom are the problems faced by teacher and students in learning writing.